Characterization of women with preconceptional risk (Revista científica Olimpia, 2026)
Introduction: Preconception reproductive risk is the probability that a woman will suffer harm to her health or the product of conception during the reproductive process. Objective: To characterize women with preconception reproductive risk in 9 Family Medicine Offices of Basic Work Group 2 of the René Vallejo Ortiz University Polyclinic, from January to March 2024. Method: A descriptive, retrospective, cross-sectional study was conducted. The study population consisted of 1,432 patients of childbearing age (12-49 years old) in the study area, from which a sample of 749 women with preconception reproductive risk was selected. The following variables were studied: age, level of education, adverse obstetric history, personal medical history, preconception reproductive risk stratification, and whether or not they were under medical supervision. Results: The study population was predominantly 12 to 14 years old. University students were the most prevalent among women. A short interpregnancy interval was the most common adverse obstetric history, and hypertension was the most frequent chronic non-communicable disease. Of the 414 cases stratified using the Pregestogram risk assessment, 363 are currently under control. Conclusions: Adolescence, a short interpregnancy interval, and hypertension contribute to the development of reproductive risks. Identifying these factors allows for adequate management and follow-up of these patients.
Keywords: fertile age, reproductive risk factors, preconception risk, health promotion, prevention.